Re-globalisation : when China meets the world again - Wang, Dong, 1977-; Cao, Dejun (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Since the end of the Cold War, globalisation has been the dominant political and economic trend. But what is China's role in globalisation? What is China's vision of the world? This title offers a fresh and stimulating account of how China's involvement in globalisation has changed over time, and how its role in leading the "re-globalisation" process is profoundly reshaping the world. Introducing an innovative theoretical framework in the shape of "re-globalisation", this book discusses China's strategies and challenges while interacting with the international community. The book provides several illuminating case studies, such as the Belt and Road Initiative (BRI), the Asian Infrastructure Investment Bank (AIIB), and the strategies of the Chinese technology firm Alibaba. Rich in data and bold in argument, the book provides an extraordinarily dynamic depiction of how China's encounter with the outside world has not only transformed itself, but also reshaped the global order. As the first systemic and book-length study of "re-globalisation", this volume will appeal to researchers and students of politics and Chinese studies, and contemporary Chinese politics in particular"--
Embracing globalisation and China's narrative -- From globalisation to re-globalisation -- Inclusive development and interconnection thinking -- The Belt and Road Initiative and global governance -- The Asian Infrastructure and Investment Bank pushes forward re-globalisation -- Digital economy 2.0 and Alibaba's globalisation story -- The mechanism of reversal pressure and the experience of special economic zones in China -- Embracing the era of re-globalisation -- Conclusion. Re-globalisation: when China meets the world again.
Translation of: Zai quan qiu hua : li jie Zhongguo yu shi jie hu dong de xin shi jiao.
OCLC-licensed vendor bibliographic record.
Keywords: Globalization -- China; China -- Economic conditions -- 2000-; China -- Foreign economic relations; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Globalization